Effect Of Transverse Abdominis Plane Block With 0.25% Bupivacaine On Post-Operative Opioid Consumption After Cesarean Section: A Prospective Study - Khalid, Muhammad; Feroze, Faheem; Faheem, Muhammad Shaheer Bin; Faheem, Saadia; Farooq, Saeed; Khalid, Maliha (Journal of Rawalpindi Medical College, 2025)
Objective: Transverse Abdominis Plane (TAP) block is a technique that can offer post-operative analgesia to patients who have had surgical procedures involving incisions made in the infra-umbilical region. In our study, we investigated whether or not a TAP block administered in conjunction with 0.25% bupivacaine was effective as an analgesic during the full 24-hour postoperative period after cesarean section. Methods: 100 patients undergoing spinal anaesthesia for caesarean section were randomly chosen to receive TAP block (50 patients in each group). Following surgical intervention, a bilateral TAP plane block was carried out by giving 0.25% bupivacaine to Group A patients and 0.9% normal saline to Group B patients (10 ml on each side). The procedure was guided by ultrasonography. An investigator blinded to the procedure evaluated the post-operative visual analogue scale VAS pain score of each patient and noted the amount of tramadol demanded over the next twenty-four hours. Results: Patients who received TAP block with 0.25% bupivacaine had a significantly lower post-operative VAS score at first analgesic request time, at 12 hours and 24 hours as compared to those patients who received normal saline (p <0.05). The mean consumption of intravenous opioid (tramadol) given during 24 hours by the surgical ICU staff was significantly decreased in Group A as compared to Group B (p <0.05). Conclusion: Ultrasound-guided bilateral TAP block with 0.25% bupivacaine lowers postoperative opioid analgesic intake in patients undergoing caesarean section. Keywords: Bupivacaine, Cesarean section, Prospective study